1998
DOI: 10.1111/j.1540-8159.1998.tb01079.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Effects of Intrapericardial Infusion of Endothelin‐1

Abstract: Recently, extremely high levels of endothelin-1 (ET-1) were detected in the pericardial fluid of patients undergoing open-heart surgery. ET-1 has been suggested to have direct arrhythmogenic effect on myocardium. The aim of the present study was to examine the putative arrhythmogenic effect of intrapericardial infusion of ET-1 in anesthetized dogs (n = 15). In preliminary experiments, ET-1 (0.125-1.0 nmol/min, n = 7) was infused into the closed pericardial sack for 40 min. ET-1 induced non-sustained and/or sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 12 publications
1
8
0
2
Order By: Relevance
“…Ventricular hypertrophy is associated with an increased incidence of spontaneous ventricular arrhythmias, cardiovascular events and arrhythmia‐related deaths [1, 2] as well as greater vulnerability to the arrhythmogenic effects of acute ischaemia [3, 4]. Endothelin‐1 (ET‐1) is an important mediator of hypertrophy [5, 6] and has an acute pro‐arrhythmic effect on its own and in the setting of ischaemia [7–10]. Several mechanisms have been proposed for the detrimental effects of ET‐1: ( i ) ET‐1 has direct toxic effects on cardiac myocytes [11, 12]; ( ii ) ET‐1 causes hypertrophy of cardiac myocytes [5, 6] and increases myocardial fibrosis [13, 14]; ( iii ) ET‐1 has a long‐term positive inotropic effect in rats with congestive heart failure (CHF), and thus may contribute to the progression of CHF by increasing myocardial energy utilization [15]; ( iv ) ET‐1 administration induces ventricular arrhythmias [16].…”
Section: Introductionmentioning
confidence: 99%
“…Ventricular hypertrophy is associated with an increased incidence of spontaneous ventricular arrhythmias, cardiovascular events and arrhythmia‐related deaths [1, 2] as well as greater vulnerability to the arrhythmogenic effects of acute ischaemia [3, 4]. Endothelin‐1 (ET‐1) is an important mediator of hypertrophy [5, 6] and has an acute pro‐arrhythmic effect on its own and in the setting of ischaemia [7–10]. Several mechanisms have been proposed for the detrimental effects of ET‐1: ( i ) ET‐1 has direct toxic effects on cardiac myocytes [11, 12]; ( ii ) ET‐1 causes hypertrophy of cardiac myocytes [5, 6] and increases myocardial fibrosis [13, 14]; ( iii ) ET‐1 has a long‐term positive inotropic effect in rats with congestive heart failure (CHF), and thus may contribute to the progression of CHF by increasing myocardial energy utilization [15]; ( iv ) ET‐1 administration induces ventricular arrhythmias [16].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the results obtained with different ET receptor blockers indicate that the haemodynamic responses to high glucose were mediated mainly by the ET B receptor, whereas the electrical responses were mediated by the ET A receptor. That ET-1 lengthens the cardiac QT interval has been reported previously Geller et al 1998), however the link to high glucose levels is novel. Since a high glucose concentration induces QT prolongation by increasing cardiac oxidative stress (D'Amico et al 2001), and oxidative stress is one determinant of the increased ET-1 production (Kahler et al 2000;Chen et al 2000) we propose that high glucose causes the increase in cardiac ET-1 levels and this in turn contributes to QT prolongation, by stimulating its own pathway(s).…”
Section: Discussionmentioning
confidence: 85%
“…Prior studies have demonstrated pharmacologic response following epicardial (EC) application of antiarrhythmic drugs [714], proarrhythmic agents [15, 16], vasodilators [17–21], and antiproliferative chemotherapeutics [22]. Other studies have demonstrated favorable pharmacokinetics, with elevated myocardial drug levels and minimal peripheral concentration, when drug is given to the pericardial sac [23–28].…”
Section: Introductionmentioning
confidence: 99%